IMMUNEPOTENT CRP induces cell cycle arrest and caspase-independent regulated cell death in HeLa cells through reactive oxygen species production - Martínez Torres, Ana Carolina; Reyes Ruiz, Alejandra; Benítez Londoño, Milena; Franco Molina, Moisés Armides; Rodríguez Padilla, María Cristina (2018)
Abstract Background: Regulated cell death (RCD) is a mechanism by which the cell activates its own machinery to self-destruct. RCD is important for the maintenance of tissue homeostasis and its deregulation is involved in diseases such as cervical cancer. IMMUNEPOTENT CRP (I-CRP) is a dialyzable bovine leukocyte extract that contains transfer factors and acts as an immunomodulator, and can be cytotoxic to cancer cell lines and reduce tumor burden in vivo. Although I-CRP has shown to improve or modulate immune response in inflammation, infectious diseases and cancer, its widespread use has been limited by the absence of conclusive data on the molecular mechanism of its action. Methods: In this study we analyzed the mechanism by which I-CRP induces cytotoxicity in HeLa cells. We assessed cell viability, cell death, cell cycle, nuclear morphology and DNA integrity, caspase dependence and activity, mitochondrial membrane potential, and reactive oxygen species production. Results: I-CRP diminishes cell viability in HeLa cells through a RCD pathway and induces cell cycle arrest in the G2/M phase. We show that the I-CRP induces caspase activation but cell death induction is independent of caspases, as observed by the use of a pan-caspase inhibitor, which blocked caspase activity but not cell death. Moreover, we show that I-CRP induces DNA alterations, loss of mitochondrial membrane potential, and production of reactive-oxygen species. Finally, pretreatment with N-acetyl-L-cysteine (NAC), a ROS scavenger, prevented both ROS generation and cell death induced by I-CRP. Conclusions: Our data indicate that I-CRP treatment induced cell cycle arrest in G2/M phase, mitochondrial damage, and ROS-mediated caspase-independent cell death in HeLa cells. This work opens the way to the elucidation of a more detailed cell death pathway that could potentially work in conjunction with caspase-dependent cell death induced by classical chemotherapies. Keywords: I-CRP, Bovine dyalisable leukocyte extract, bDLE, Cell death, Cervical cancer, Immunotherapy, Transfer factor, Immunomodulator, Apoptosis